Teaching systems thinking to protect wildlife: a pilot study in West Bengal’s secondary schools - Iyer, Sangita; Rizzolo, Jessica Bell; Kshettry, Aritra; Ireland, Liza; Suman, Shalvi (Frontiers in Ethology, 2026)
Conventional school curricula fragment knowledge into siloed subjects and rely on rote learning, leaving students ill-equipped to address complex socio-ecological issues such as human-elephant conflict. We tested the hypothesis that a topic-based curriculum—grounded in nine ecological principles—could enhance eco-literacy, empathy, and creative problem-solving among secondary students. Between October 2022 and February 2024, our multidisciplinary team co-created the Elephants and People unit and implemented it across three sequential phases: (1) a three-day teachers’ training workshop (for 38 teachers from 18 schools) employing slow pedagogy, Appreciative Inquiry, backcasting, World Café dialogues, experiential outdoor games, and daily benchmarking; (2) teacher-led classroom implementation in five human-elephant-conflict-zone schools, organizing nature immersion, journaling, screening Asian Elephants 101 film series (subtitled in local language), and action research; and (3) an advanced curriculum design workshop for teachers, producing locally tailored, interdisciplinary units grounded in systems thinking. Benchmarking scores rose from a median of 2–3/10 to 7–8/10, reflecting significant gains in teacher confidence and knowledge. Classroom observations revealed 83% of participating schools and 77% of teachers fully adopted the pedagogy. Student reflections and essays showed increased empathy and innovative ideas for coexistence. This research could help create a paradigm shift in curriculum design—from fragmented, anthropocentric content to holistic, eco-centric learning—inspiring pro-conservation attitudes, restoring students’ innate creativity, and deepening their sense of interdependence with nature. Scaling this framework through multidisciplinary curriculum integration and systems thinking workshops for teachers offers a promising path to transform education into a catalyst for sustainable human-wildlife coexistence.